Effects of kinesio tape on kinesiophobia, balance and functional performance of athletes with post anterior cruciate ligament reconstruction: a pilot clinical trial - Gholami, M.; Kamali, F.; Mirzeai, M.; Motealleh, A.; Shamsi, M. B. (BMC Sports Science, Medicine and Rehabilitation, 2020)
Background: Anterior cruciate ligament trauma is one of the most common knee injuries in professional athletes. This study aimed to investigate the effects of kinesio taping on kinesiophobia, balance, and functional performance in athletes after anterior cruciate ligament reconstruction. Methods: This randomized, placebo-controlled clinical trial was performed on 20 athletes with anterior cruciate ligament reconstruction (mean age 32.3 ± 6.2 years) at the time of return to sport. The subjects were randomly assigned to the kinesio tape (KT) group (n = 10) or placebo KT group (n = 10).